2022
DOI: 10.1186/s13049-022-01031-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the cervical collar from alpine rescue protocols? A biomechanical non-inferiority trial in real-life mountain conditions

Abstract: Background Alpine skiing rescues are challenging because of the mountainous environment and risks of cervical spine motion (CSM) induced during victims’ extrications (EXs) and downhill evacuations (DEs). The benefits of applying a cervical collar (CC) over manual in-line stabilization without CC (MILS) in terms of spinal motion restriction during simulated alpine rescues are undocumented. Our hypothesis was that CSM recorded using MILS alone is non-inferior to CSM recorded with a CC according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Grenier et al note that the biomechanical benefits of a cervical collar are marginal in the ski environment, cervical collar use negatively affects rescue time, and manual in-line stabilization (motion restriction) had less cervical spine motion than applying a cervical collar. 71 Rigid cervical collars are also difficult to apply correctly and are often incorrectly applied even by those who believe they are competent in this skill. When studied, 89% of providers made at least 1 error in placement, and competence was not related to confidence.…”
Section: Effectiveness Of the Cervical Collar In Immobilization Of Th...mentioning
confidence: 99%
“…Grenier et al note that the biomechanical benefits of a cervical collar are marginal in the ski environment, cervical collar use negatively affects rescue time, and manual in-line stabilization (motion restriction) had less cervical spine motion than applying a cervical collar. 71 Rigid cervical collars are also difficult to apply correctly and are often incorrectly applied even by those who believe they are competent in this skill. When studied, 89% of providers made at least 1 error in placement, and competence was not related to confidence.…”
Section: Effectiveness Of the Cervical Collar In Immobilization Of Th...mentioning
confidence: 99%
“…This is a concern, especially as it was demonstrated that the validity of subjective performance scores from both rescuers and a simulated patient in a context of SMR is poor compared with objective measures of motion [ 4 ]. Providing immediate or deferred objective feedback on the quality and effectiveness of SMR applied during pre-hospital care scenarios by healthcare professionals could help to identify the most effective technique in addition to improving SMR techniques’ execution [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%